Natural Variation of the Circadian Clock in Neurospora - Koritala, Bala S. C. (Adv Genet, 2017)
Most living organisms on earth experience daily and expected changes from the rotation of the earth. For an organism, the ability to predict and prepare for incoming stresses or resources is a very important skill for survival. This cellular process of measuring daily time of the day is collectively called the circadian clock. Because of its fundamental role in survival in nature, there is a great interest in studying the natural variation of the circadian clock. However, characterizing the genetic and molecular mechanisms underlying natural variation of circadian clocks remains a challenging task. In this chapter, we will summarize the progress in studying natural variation of the circadian clock in the successful eukaryotic model Neurospora, which led to discovering many design principles of the molecular mechanisms of the eukaryotic circadian clock. Despite the success of the system in revealing the molecular mechanisms of the circadian clock, Neurospora has not been utilized to extensively study natural variation. We will review the challenges that hindered the natural variation studies in Neurospora, and how they were overcome. We will also review the advantages of Neurospora for natural variation studies. Since Neurospora is the model fungal species for circadian study, it represents over 5 million species of fungi on earth. These fungi play important roles in ecosystems on earth, and as such Neurospora could serve as an important model for understanding the ecological role of natural variation in fungal circadian clocks.